2013
DOI: 10.1371/journal.pone.0050175
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Sensitizes Bladder Cancer Cells to HCPT Treatment In Vitro and In Vivo via ATM/NF-κB/IKK Pathway-Induced Apoptosis

Abstract: Bladder cancer is the most common malignant urological disease in China. Hydroxycamptothecin (HCPT) is a DNA topoisomerase I inhibitor, which has been utilized in chemotherapy for bladder cancer for nearly 40 years. Previous research has demonstrated that the isoflavone, genistein, can sensitize multiple cancer cell lines to HCPT treatment, such as prostate and cervical cancer. In this study, we investigated whether genistein could sensitize bladder cancer cell lines and bladder epithelial cell BDEC cells to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Flow cytometric analysis revealed that the number of apoptotic cells increased from 20.89% (following treatment with 2.5 nM HCPT) to 97.66% (following treatment with 20 nM HCPT) in a dose-dependent manner. So consistent with earlier observations in other tumor cells [19][20][21][22][23][24], we found that HCPT inhibits the proliferation and viability of SMS-KCNR cells by inducing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Flow cytometric analysis revealed that the number of apoptotic cells increased from 20.89% (following treatment with 2.5 nM HCPT) to 97.66% (following treatment with 20 nM HCPT) in a dose-dependent manner. So consistent with earlier observations in other tumor cells [19][20][21][22][23][24], we found that HCPT inhibits the proliferation and viability of SMS-KCNR cells by inducing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Induction of apoptosis in tumor cells is a promising chemopreventive or chemotherapeutic strategy [17,18]. Previous studies have demonstrated that HCPT is able to induce apoptosis in cells of various tumor types, including colon, liver, gastric, prostate and bladder cancer, as well as melanoma [19][20][21][22][23][24]. However, only one study regarding HCPT-induced apoptosis of NB cells has been conducted [25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, genistein can induce apoptosis through ATM signaling. 20,21 In T cells etoposide treatment through ATM can also cause apoptosis. 22 ATM signaling can also facilitate liver damage in already damaged fibrotic livers.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavone genistein exerts its effects by regulation of multiple signaling pathways. We and other investigators have found that isoflavone could significantly inhibit the activation of AR, Akt, and NF-κB in PCa cells and interrupt the crosstalk between these three signaling pathways in vitro [3035]. By in vivo studies, isoflavone has been found to inhibit prostate tumor growth through inhibition of AR activation and AR downstream gene expression [36, 37].…”
Section: The Role Of Nutraceuticals In the Inhibition Of Pcamentioning
confidence: 99%